VIOLÊNCIA E INTOLERÂNCIA RELIGIOSA NO BAIXO IMPÉRIO: OS LEVANTES DE CONSTANTINOPLA SOB O GOVERNO DE CONSTÂNCIO II (337-361) - da Silva, Gilvan Ventura (PHOÎNIX, 2020)
The religious intolerance and the use of violence against different kinds of believers are ordinary phenomena in the Later Roman Empire. In fact, at that period of Roman history, hate between Christians, Pagans and Jews becomes stronger. At the same time, the imperial power decides to intervene systematically in religious matters. With this article, we aim at discussing the reasons by which we realize an increasing of religious intolerance at the Empire since the Third Century at least. Secondly, we intend to comprehend how the violence was manipulated by the urban mobs as a symbolical resource. ln order to do it, we analyze the violent struggles which occurred at Constantinople during the reign of Constantius II (337-361), especially the conflicts involving Nicene and Arian supporters.